1986
DOI: 10.1017/s0022112086002197
|View full text |Cite
|
Sign up to set email alerts
|

The hydraulics of two flowing layers with different densities

Abstract: This is a theoretical and experimental study of the basic hydraulics of two flowing layers. Unlike single-layer flows, two-layer flows respond quite differently to bottom depth as opposed to width variations. Bottom-depth changes affect the lower layer directly and the upper layer only indirectly. Changes in width can affect both layers. In fact for flows through a contraction control two distinct flow configurations are possible; which one actually occurs depends on the requirements of matching a downstream f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
322
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(332 citation statements)
references
References 7 publications
10
322
0
Order By: Relevance
“…In the full-depth hydrographic profiles the Medi'terranean water tongue is apparent as a layer of nearly constant salinity in the approximate 02 (potential temperature referenced to 2000 dbar) range of 8ø-10øC (see Figure 4) In the case of an inviscid steady two-dimensional flow along a channel of slowly varying geometry a horizontally asymmetric density distribution (i.e., differing reservoir conditions) implies that the flow is (hydraulically) controlled [Armi, 1986]. Pratt [1986] The simple one-and-a-half layer reduced gravity model with zero upstream potential vorticity introduced by Whitehead et al [1974] is considered adequate for this purpose, mainly because it is the simplest model of rotating hydraulics, which has been tested in similar contexts [Whitehead, 1997].…”
Section: Regional Hydrography and Flow Fieldmentioning
confidence: 99%
“…In the full-depth hydrographic profiles the Medi'terranean water tongue is apparent as a layer of nearly constant salinity in the approximate 02 (potential temperature referenced to 2000 dbar) range of 8ø-10øC (see Figure 4) In the case of an inviscid steady two-dimensional flow along a channel of slowly varying geometry a horizontally asymmetric density distribution (i.e., differing reservoir conditions) implies that the flow is (hydraulically) controlled [Armi, 1986]. Pratt [1986] The simple one-and-a-half layer reduced gravity model with zero upstream potential vorticity introduced by Whitehead et al [1974] is considered adequate for this purpose, mainly because it is the simplest model of rotating hydraulics, which has been tested in similar contexts [Whitehead, 1997].…”
Section: Regional Hydrography and Flow Fieldmentioning
confidence: 99%
“…Inviscid hydraulic control theory was expanded to two layers by Armi [1986] and Farmer and Armi [1986].…”
Section: Two Frictionless Layersmentioning
confidence: 99%
“…First, in the absence of mixing, viscosity, and friction, internal hydraulic theory [Wood, 1970;Armi, 1986;Armi and Farmer, 1986;Lawrence, 1990;Dalziel, 1991] can be used to predict the velocities and depths of two distinct layers. Alternatively, if the exchange flow is dominated by turbulent mixing, we can find a solution where velocity is limited by turbulent eddy viscosity, and transport of mass is due to a combination of advection and turbulent diffusion [Cotmack et al, 1974;Offricer, 1976 Internal hydraulic theory is based on a simple balance between inertial and buoyancy forces.…”
Section: Introductionmentioning
confidence: 99%
“…-+ It can be shown that only two of (4), (5), and (6) are independent [Armi, 1986]. A flow is said to be maximal if it has both a virtual control and a topographic control [Armi and Farmer, 1987].…”
Section: Introductionmentioning
confidence: 99%